Managing Superficial Distal Medial Collateral Ligament Insufficiency in Primary Total Knee Arthroplasty Using Bone Staples - White, Kevin T.; Fleischman, Andrew; Ackerman, Colin T.; Chen, Antonia F.; Rothman, Richard H. (The Journal of Knee Surgery, 2019)
Superficial medial collateral ligament (MCL) injury is an occasional intraoperative complication during total knee arthroplasty (TKA) that can lead to failure. Although previous studies have recommended complex repair or conversion to a constrained implant, the authors evaluated results of superficial distal MCL reapproximation using bone staples. Records of 31 patients who underwent staple reapproximation for superficial MCL avulsion from the tibial attachment during primary TKA from 2005 to 2015 were reviewed. They were compared with 685 patients who underwent uncomplicated TKA (primary control) and 18 who underwent revision TKA for instability (secondary control). Subjective knee instability was assessed with a patient questionnaire, and other end points included revision for instability or stiffness and manipulations under anesthesia. The authors prospectively collected Knee injury and Osteoarthritis Outcome Score (KOOS) and visual analog scale satisfaction scores. The mean follow-up was 2.6 years. No patients treated with staple repair required revision for instability, whereas two patients were revised in the primary control. Subjective instability was reported in 19.2% of staple repair patients compared with 24.2 and 46.2% of patients in the primary and secondary controls. The mean KOOS for the staple group was 71.7 points, 77.3 for the primary control, and 49.3 for the secondary. KOOSs for the staple group were 5.6 points lower than the primary control, but 22.4 points higher than the secondary. Staple reapproximation is a simple and effective method for repairing the superficial distal MCL in primary TKA. The rate of instability and functional outcomes was comparable to uncomplicated primary TKA.
Keywords: medial collateral ligament; intraoperative complications; knee; arthroplasty; bone staples